Pengamanan Citra Dengan Kombinasi Modified Serpent IWT Dengan Modified Logistic Chaotic Map - Kelvin Lysander; Allwin M Simarmata; Denniel Lusandy; Iswandi Iswandi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Abstract Cryptographic algorithms can be used to secure images. One of the cryptographic algorithms that can be used to encrypt images is the Serpent algorithm. However, the Serpent algorithm requires a long encryption and decryption process. In addition, encryption alone is not enough because it will raise suspicions so that the information will be vulnerable to being stolen. So we need a steganography technique such as the Integer Wavelet Transform (IWT) method. The secret image will be encrypted first using the Modified Serpent method, where the Serpernt modification changes the byte substitution transformation process (DES S-box) into a list of 257 prime numbers which has 128 generators to be used as keys in each round. In the insertion process using the IWT method, it is necessary to determine the position of the bits and pixels on the cover image where a message will be inserted. To determine the position, the chaos function is used. After that, the extraction process can be carried out on the stego image generated in the embedding process to recover the bits stored in it. The set of bits can be decrypted so that the original secret image will be recovered.